2018
DOI: 10.1080/1745039x.2018.1507977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary nitrogen level and source on mRNA expression of urea transporters in the rumen epithelium of fattening bulls

Abstract: This paper aims to study the effect of the dietary treatments on mRNA expression of urea transporter B (UT-B) and some aquaporins (AQP) in rumen epithelium of Italian Simmental young bulls. Eighty animals allocated to 16 pens were fed from about 500 to 650 kg body weight with four experimental diets, which resulted from the combination of two crude protein levels (125 and 110 g/kg dry matter, diets M and L, respectively) and two nitrogen sources (soybean meal (SBM) or SBM partly replaced by an isonitrogenous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…(Coyle et al, 2016). Overall, the abundant AQP3 transcript expression agrees with previous studies (Røjen et al, 2011;Saccà et al, 2018) and suggests that AQP3 may play an important role in bovine rumen function. To test for alternatively spliced AQP3 transcripts, we designed a forward primer against exon 1 (F1) and a reverse primer against exon 6 (R6).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…(Coyle et al, 2016). Overall, the abundant AQP3 transcript expression agrees with previous studies (Røjen et al, 2011;Saccà et al, 2018) and suggests that AQP3 may play an important role in bovine rumen function. To test for alternatively spliced AQP3 transcripts, we designed a forward primer against exon 1 (F1) and a reverse primer against exon 6 (R6).…”
Section: Resultssupporting
confidence: 87%
“…Therefore, more detailed experiments are needed to comprehensively characterize the abundance and localization of AQGP. As stated, various studies (Røjen et al, 2011;Berends et al, 2014;Walpole et al, 2015;Saccà et al, 2018) have previously indicated AQP3 transcription is more responsive to diets. Therefore, in this present study we investigated the expression, abundance and localization of AQP3 transporters in the bovine rumen.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Their findings confirmed that UT-A or UT-B transporters were associated with urea transport in ruminal epithelia. Furthermore, when dietary treatments contain urea, AQP-3 gene expression is down-regulated, suggesting a portion of urea flux occurs via facilitated diffusion through AQP ( Saccà et al., 2018 ). The expression of UT-B and AQP-3 is up-regulated as an incremental supplementation of calves with solid feeds with minimal nitrogen contents, which is also an indication of facilitated urea recycling in ruminants ( Berends et al., 2014 ).…”
Section: Physiological Roles and Structures Of Urea Transportersmentioning
confidence: 99%
“…The activity of urea transporters are also affected by different dietary nitrogen contents. Saccà et al. (2018) and Røjen et al.…”
Section: Factors Affecting Urea Hydrolysis and Transportation In The Rumenmentioning
confidence: 99%